Pengaruh Pemberian Makanan Tambahan Biskuit Ikan Patin Tempe dalam Pencegahan Stunting pada Balita Suku Anak Dalam (SAD) di Desa Nyongan Kabupaten Muaro Jambi - Aisah Aisah; Kasyani Kasyani; Tuhu Perwitasari; Suci Rahmani Nurita (Jurnal Akademika Baiturrahim Jambi, 2026)
Stunting is a disorder of child growth and development due to chronic malnutrition and repeated infections, which is characterized by length or height below the standards set by the Ministry of Health. Providing Supplementary Food to meet the nutritional adequacy of toddlers by providing additional food for toddlers, and not to replace the toddler's daily main food. The purpose of this study was to see the effect of giving catfish biscuits to prevent stunting in SAD toddlers in Nyogan Village. The research design used in this study was a Quasi Experiment with a Pretest - Posttest research design to see the difference in nutritional status of toddlers before and after being given catfish biscuits, this study was conducted from April to November 2024 in Nyogan Village, the research sample was all SAD toddlers in Nyogan Village. The results of the statistical test in the intervention group obtained a p value = 0.000, it can be concluded that there is a difference between the nutritional status of toddlers in the first and second measurements. The results of the statistical test in the control group obtained a p value = 0.125, it can be concluded that there is no difference between the nutritional status of toddlers in the first and second measurements. The conclusion is that giving catfish biscuits can improve the nutritional status of SAD toddlers in Nyogan Village